Epistemologi Tafsir Ishari: Kajian terhadap Kitab Haqã’iq al-Tafsĩr karya Abu ‘Abd Al-Rahman Al-Sulamî - T Mairizal (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2025)
This study examines Haqā’iq al-Tafsīr by Abu ‘Abd al-Rahman al-Sulamī as a classical representation of tafsīr ishârî, rooted in Sufi intuition while maintaining alignment with ẓāhir (exoteric) interpretation. Utilizing a library research method, this work explores both primary and secondary sources to investigate the epistemological foundations and the interpretive contribution of this text within the broader Islamic exegetical tradition. Despite its mystical orientation, the tafsīr remains within the bounds of the Sharia and avoids the deviations often associated with bāṭinī exegesis. In contemporary discourse, Haqā’iq al-Tafsīr offers valuable insight into promoting religious moderation through a spiritually rich yet normatively grounded, inclusive approach to Islamic understanding.